Fibroblast GATA-4 and GATA-6 promote myocardial adaptation to pressure overload by enhancing cardiac angiogenesis - Dittrich, Gesine M.; Froese, Natali; Wang, Xue; Kroeger, Hannah; Wang, Honghui; Szaroszyk, Malgorzata; Malek Mohammadi, Mona; Cordero, Julio; Keles, Merve; Korf-Klingebiel, Mortimer; Wollert, Kai C.; Geffers, Robert; et al. (Basic research in cardiology, 2021)
Heart failure due to high blood pressure or ischemic injury remains a major problem for millions of patients worldwide. Despite enormous advances in deciphering the molecular mechanisms underlying heart failure progression, the cell-type specific adaptations and especially intercellular signaling remain poorly understood. Cardiac fibroblasts express high levels of cardiogenic transcription factors such as GATA-4 and GATA-6, but their role in fibroblasts during stress is not known. Here, we show that fibroblast GATA-4 and GATA-6 promote adaptive remodeling in pressure overload induced cardiac hypertrophy. Using a mouse model with specific single or double deletion of Gata4 and Gata6 in stress activated fibroblasts, we found a reduced myocardial capillarization in mice with Gata4/6 double deletion following pressure overload, while single deletion of Gata4 or Gata6 had no effect. Importantly, we confirmed the reduced angiogenic response using an in vitro co-culture system with Gata4/6 deleted cardiac fibroblasts and endothelial cells. A comprehensive RNA-sequencing analysis revealed an upregulation of anti-angiogenic genes upon Gata4/6 deletion in fibroblasts, and siRNA mediated downregulation of these genes restored endothelial cell growth. In conclusion, we identified a novel role for the cardiogenic transcription factors GATA-4 and GATA-6 in heart fibroblasts, where both proteins act in concert to promote myocardial capillarization and heart function by directing intercellular crosstalk.
Gesehen am 15.08.2023